PATTERNS OF ACUTE POISONING AMONG PATIENTS TREATED IN THE EMERGENCY WARDS OF A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY - Revathi, Devi; Reddy, Sathvika; Prasanna V, Lakshmi; Ramesh, Aruna C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Poisoning is a growing health-care burden in developing countries like India. Predicting the nature of the intention behind poisoning and type of poisoning agent involved will help in facilitating appropriate treatment measures, hence, improving the patient's quality of life. Methods: The prospective, observational study was conducted in a tertiary care multispecialty hospital for 6 months from November 2016 to April 2017 and involved a total of 133 patients. Treatment and outcomes of the patients were collected, documented in a data collection form. Chi-square test and logistic regression analysis were applied. Results: The mean age of the study participants was 27.76Â±15.5 with predominance seen in age groups of <30 years (59.3%), females (52.6%), and married (49.6%). Intentional poisoning (69.1%) through oral ingestion (81.2%) of medications (51.6%) in solid forms (60.2%) was predominant. Patients presenting with systemic manifestations (70.4%) arrived in a time duration >1 h (66.2%), received first aid (62.4%), and supportive care (52.7%). Higher ingestion of physical forms was significantly observed in both single (OR: 4.5) and married (OR: 3). The outcomes were correlated with poison severity score and patients with mild symptoms recovered (60.9%). Conclusion: The use of medicines for intentional poisoning continues to be rampant in younger age groups and married individuals. Educational programs with more accentuation on the data regarding toxic substances along with preventive measures are to be implemented to make mindfulness among the overall population.